Ultraconformal Horizontal Zinc Deposition toward Dendrite‐Free Anode. Issue 1 (7th October 2022) - Zou, Juan; Zeng, Ziyue; Wang, Chenyang; Zhu, Xiaohui; Zhang, Jiaqian; Lan, Haihui; Li, Linyang; Yu, Yantao; Wang, Huiliu; Zhu, Xiaolong; Zhang, Yile; Zeng, Mengqi; et al.
Abstract : Aqueous zinc (Zn)‐ion batteries (ZIBs) have been considered as the most promising candidate for large‐scale energy storage system. However, the severe and uncontrollable dendrite growth of Zn anodes hinders the practical application. Herein, an ultraconformal horizontal Zn deposition is achieved, which is profiting from the epitaxial interface (InGaZn6 O9 ) formed via spontaneously alloying between liquid Ga–In alloy (EGaIn) and Zn. The exposed (0016) plane of InGaZn6 O9 matches well with (002) plane of Zn, inducing horizontal and dense Zn deposition. The resultant anode endows with prolonged cycling stability, and the full battery paired with MnO2 exhibits a stable lifespan over 4400 cycles at 5 A g −1 . Meanwhile, the self‐formed ultraconformal interface realizes 360° no dead angle protection of anode, which is promising in flexible electronics. And there is no obvious capacity recession of the pouch cell even after bending 180°, demonstrating impressive flexibility. More importantly, the interface can be simply fabricated over a large area, displaying the large‐scale viability. The tailored approach delivers a constructive guideline for dendrite‐free Zn anode, showing great potential in the industrial production. Abstract : Herein, an effective strategy is reported to accomplish ultraconformal horizontal Zn deposition via spontaneous formation of epitaxial interface. It can achieve 360° no dead angle protection to suppress the growth of Zn dendrites. The resulted anode exhibits excellent long‐term cycling stability and the corresponding full battery shows outstanding flexibility. The simple approach makes the large‐scale application feasible.